1989
DOI: 10.1016/s0022-5347(17)41016-0
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Formalin for Hemorrhagic Cystitis: Analysis of Therapy

Abstract: In an extensive search of the literature 235 cases of intractable hemorrhagic cystitis treated with intravesical formalin were identified. Effectiveness of therapy, rate of recurrence of hematuria, morbidity and mortality were analyzed with respect to concentration of formalin and to the etiology of hematuria. Increasing concentrations of formalin slightly improved effectiveness of therapy and reduced the rate of recurrence of hematuria. However, this often resulted in an increase in morbidity. When patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
7

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 26 publications
0
45
0
7
Order By: Relevance
“…19,20,21,22,23,24 Intravesical formalin instillation is performed under general or regional anesthesia once vesicoureteral reflux has been excluded. It causes precipitation of cellular proteins in the mucosa, producing an occlusive and fixative action on telangiectatic tissue and small capillaries.…”
Section: Formalinmentioning
confidence: 99%
“…19,20,21,22,23,24 Intravesical formalin instillation is performed under general or regional anesthesia once vesicoureteral reflux has been excluded. It causes precipitation of cellular proteins in the mucosa, producing an occlusive and fixative action on telangiectatic tissue and small capillaries.…”
Section: Formalinmentioning
confidence: 99%
“…[14][15][16] Few have shown an encouraging effect with acceptable side-effects. Case reports about oral estrogen as an effective treatment of HC have prompted us to try this modality in affected patients.…”
mentioning
confidence: 99%
“…9,11,12,[15][16][17] In their comprehensive review of the 235 previously reported cases of formalin use, Donahue and Frank (1989) identified a trend towards increasing complete response rates with 10% intravesical formalin (83% complete response), as compared to 5% formalin (78% complete response) or 1% formalin (71% complete response) solutions, although this was not statistically significant. 16 Here, we identified a success rate of 63% at a median followup of eight months with the initial use of 1% formalin. Notably, dose escalation to 4% was used in only one patient.…”
Section: Discussionmentioning
confidence: 99%